RDT-RT Three-Phase Smart and Powerful Digital Voltage Stabilizer: 3-Phase Voltage Stabilizer for Industry - Rizki Kurniawan Firmansyah; Moh Faiz Rosyidi; Ardian Maulana W.A; Akhmad Faldy Galuh Dwy Alfaris; Muhammad Lhuhuri Mustofani (Takaza Innovatix Labs Ltd., 2025)
Voltage instability in industrial power distribution systems causes equipment damage, operational inefficiency, and production downtime. This research evaluated the Smart Powerful Digital Stabilizer RDT-RT three-phase system implementing digital Automatic Voltage Regulator technology. Using quantitative experimental methodology, researchers tested three RDT-RT units across twelve operational scenarios generating over 300 measurements. The investigation employed high-speed oscilloscopes, power quality analyzers, and precision voltage sensors to measure output voltage stability, transient settling time, and power conversion efficiency. Static testing across input voltage range 200V to 500V demonstrated mean output accuracy of 379.8V with ±1.2V standard deviation, maintaining ±5% tolerance. Dynamic testing showed settling time below 1.3 seconds following load transients, compared to 5 to 10 seconds for conventional systems. Harmonic distortion measured 2.8 percent THD, compliant with IEEE 519 standards. Average power conversion efficiency reached 86.7 percent across operational range. Results demonstrate that digital microcontroller-based PID control combined with PWM switching substantially improves voltage regulation performance. The RDT-RT technology provides superior power quality and equipment protection essential for Industry 4.0 manufacturing environments requiring real-time process control.